Persistent DNMT3A mutation burden in DNMT3A mutated adult cytogenetically normal acute myeloid leukemia patients in long-term remission. (October 2016) - Sun, Yanjun; Shen, Hongjie; Xu, Ting; Yang, Zhen; Qiu, Huiying; Sun, Aining; Chen, Suning; Wu, Depei; Xu, Yang
Highlights: DNMT3A mutations burden existed in DNMT3Amut CN-AML patients with long-term remission. Next-generation sequencing to explore the potential leukemogenesis mechanism of DNMT3A mutation. DNMT3A mutation was an early event in the leukemogenesis. Abstract: DNMT3A mutations are frequent in cytogenetically normal acute myeloid leukemia (CN-AML) patients and can be present many years before the disease develops. However, the clinical significance of DNMT3A mutation burden in CN-AML remains unclear. In this study, 81 DNMT3A mutated adult CN-AML patients in their first complete remission (CR) were enrolled at our center from March 2005 to May 2015. All patients were identified as having DNMT3A exon 23 mutations, and R882H was the most frequent variant (n = 49, 60.49%). A total of 48 patients (48/81, 59.3%) were found to have DNMT3A mutations upon achieving CR. At the final follow-up exam, 40 patients remained in CR, 8 of which (8/81, 9.9%) were found to still have DNMT3A mutations. Analysis of the order of NPM1, FLT3-ITD and DNMT3A mutations for different disease statuses revealed that DNMT3A might be the earliest mutation in leukemic cells. In addition, we determined the possible gene aberrations in 12 de novo and 2 relapsed samples using next-generation sequencing. NPM1 (5/12, 41.7%), FLT3-ITD (5/12, 41.7%) and CEBPA mutations (4/12, 33.3%) were the most frequent coexisting mutations. In the relapsed samples, additional genes aberrations could be observed, and some of them were never reported in AML patients. The 2-year overall survival (2-OS) for 81 DNMT3A mutated CN-AML patients was 39.0%. No differences was found in 2-OS (38.2% vs 41.6%, P = 0.2256) and 2-year disease free survival (2-DFS: 28.5% vs 34.3%, P = 0.1831) between patients with negative (n = 33) and positive DNMT3A mutation findings (n = 48) at the first CR. In summary, our findings indicated that DNMT3A mutation burden could persist in adult DNMT3A mutated CN-AML patients in long-term remission and that DNMT3A mutation was the early event in the development of leukemic cells.